Analisis Hubungan Kemampuan Dasar Matematika Terhadap Hasil Belajar Statsitika - Wahyuni, Fitry; Fatimah, Ade Evi (Smart Education, 2021)
This study aims to analyze and describe the relationship between basic mathematical abilities and statistical learning outcomes. This study is an explanatory researchs with quantitative correlational research method. The subjects in this study were fifth semester students of the D3 Corporate Management study program, while the objects in this study were students' basic mathematical abilities which included algebra, calculus, and probability and student statistics learning outcomes. The data was collected using a basic mathematical ability test instrument consisting of a test of algebra, calculus and probability material as well as a test of statistical learning outcomes. The data obtained were analyzed by descriptive and inferential statistics. Inferential statistical testing using multiple linear regression test. Based on the results of data analysis, there is a positive relationship between basic mathematical abilities (algebra, calculus, and probability) on student statistics learning outcomes.